Assessing Sperm DNA Fragmentation Post-Cryopreservation in Infertility Cases - Dayal, Ram; Mehrotra, Arpit; Sood, Abhilasha (Scripta Medica, 2025)
Background/Aim: Sperm cryopreservation is an important practice utilised in many assisted reproductive techniques. The potential biological effects of cryopreservation on sperm DNA damage in infertile males need to be better understood for therapeutic optimisation. This study aimed to explore the relationship between different types of infertility, sperm DNA damage and the post-thaw survival of cryopreserved sperm. Methods: Present study initially included a total of 31 patients, wherein only 21 patients with either primary or secondary infertility and have consented for sperm cryopreservation were included, whereas patients with conditions like oligozoospermia, azoospermia and necrozoospermia were not included in the study. After a 7-days abstinence period, semen samples (from 21 patients) were collected and routine semen parameters (eg, semen volume, pH and motility) were evaluated, along with sperm DNA fragmentation analysis before cryopreservation. A few weeks later, post-thaw sperm motility was assessed for all samples. Results: The semen characteristics, including volume, pH, leukocyte count, the concentration levels of sperm and their motility were found to be similar in patients with primary and secondary infertility. However, post-thaw sperm motility was significantly lower in secondary infertility patients compared to those with primary infertility. Specifically, post-thaw motility in secondary infertility patients decreased to 43 %, a substantial reduction from 66 % in their pre-freeze state. In contrast, semen cryopreservation led to a 28 % reduction in sperm motility overall, regardless of infertility type. The freshly ejaculated semen samples showed higher sperm DNA fragmentation in case of secondary infertility patients as compared to those with primary infertility. Conclusion: The reduced post-thaw sperm motility observed in secondary infertility patients may be attributed to increased sperm DNA fragmentation in these individuals. Therapeutic interventions, such as the administration of synthetic additives to fortify semen samples, could help reduce DNA damage and improve outcomes in assisted reproductive techniques for secondary infertility patients.